A Study of Daytime Convective Vortices and Turbulence in the Martian Planetary Boundary Layer Based on Half‐a‐Year of InSight Atmospheric Measurements and Large‐Eddy Simulations. Issue 1 (26th January 2021) - Spiga, A.; Murdoch, N.; Lorenz, R.; Forget, F.; Newman, C.; Rodriguez, S.; Pla‐Garcia, J.; Moreiras, D. Viúdez; Banfield, D.; Perrin, C.; Mueller, N. T.; Lemmon, M.; et al.
Abstract: Studying the atmospheric planetary boundary layer (PBL) is crucial to understand the climate of a planet. The meteorological measurements by the instruments onboard InSight at a latitude of 4.5°N make a unique rich data set to study the active turbulent dynamics of the daytime PBL on Mars. Here we use the high‐sensitivity continuous pressure, wind, and temperature measurements in the first 400 sols of InSight operations (from northern late winter to midsummer) to analyze wind gusts, convective cells, and vortices in Mars' daytime PBL. We compare InSight measurements to turbulence‐resolving large‐eddy simulations (LES). The daytime PBL turbulence at the InSight landing site is very active, with clearly identified signatures of convective cells and a vast population of 6, 000 recorded vortex encounters, adequately represented by a power law with a 3.4 exponent. While the daily variability of vortex encounters at InSight can be explained by the statistical nature of turbulence, the seasonal variability is positively correlated with ambient wind speed, which is supported by LES. However, wind gustiness is positively correlated to surface temperature rather than ambient wind speed and sensible heat flux, confirming the radiative control of the daytime Martian PBL; and fewer convective vortices are forming in LES when the background wind is doubled. Thus, the long‐term seasonal variability of vortex encounters at the InSight landing site is mainly controlled by the advection of convective vortices by ambient wind speed. Typical tracks followed by vortices forming in the LES show a similar distribution in direction and length as orbital imagery. Plain Language Summary: InSight is a lander sent to the surface of Mars with a weather station capable, like never before, to measure pressure, temperature, and winds continuously and at high cadence. We use this InSight atmospheric data set acquired over half a Martian year, along with computer simulations, to study the intense turbulence that develops in the daytime hours on Mars. InSight detects periodic variations in the measurements of the weather station, corresponding to air motions driven by convection. We also detect a large population of 6, 000 whirlwinds passing close to the InSight lander and causing the pressure at the weather station to suddenly drop. The number of those whirlwind encounters varies from day to day, because of the random turbulence, and, on a seasonal basis, because of the varying ambient wind that transports the whirlwinds toward InSight. Unlike the population of whirlwinds, the strength of wind gusts follows the ground temperature varying with season. Whirlwinds also leave graffiti‐like dark tracks at the surface of Mars that can be imaged by satellites in the InSight region and reproduced by our numerical simulations. Key Points: We study daytime turbulence with InSight atmospheric measurements and large‐eddy simulations We identify convective cells, as well as numerous convective vortices following a power law of exponent 3.4 Seasonal variability of convective vortices controlled by wind advection and conversely turbulent gustiness correlated with surface temperature